PENGEMBANGAN MEDIA POP - UP BOOK UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS V MI MA’ARIF AT TAQWA KESAMBEN KULON WRINGINANOM GRESIK - Asyifa, Salsa Ade Nisa; Fithriyah, Ainul (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to develop a Pop-Up Book-based learning media to enhance critical thinking skills of fifth-grade students at MI Ma’arif At Taqwa in social studies, particularly in the topic of cultural diversity in Indonesia. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The media was validated by content and media experts, achieving feasibility percentages of 91.67% and 98.33%, respectively. A limited trial with 10 students showed a highly positive response with an average score of 4.39 (87.87%), categorized as